THE PREVENTIVE ROLE OF NOTARIES IN MITIGATING CORPORATE BANKRUPTCY RISK THROUGH CORPORATE DEED DRAFTING IN INDONESIA - Agustina; Bobby Christian Halim; Sayyida Faradiba Vahlevi (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2026)
: The growing complexity of business transactions has increased corporate exposure to legal risk, including bankruptcy risk arising not only from financial distress but also from weak legal architecture in corporate documents. This study examines the preventive role of Indonesian notaries in mitigating bankruptcy risk through the drafting of corporate deeds. It addresses three issues: the legal framework governing this role, its implementation in notarial practice, and the juridical and practical factors affecting its effectiveness. The research adopts a doctrinal legal method using statutory and conceptual approaches. Primary legal materials include the Notary Office Law, the Company Law, the Indonesian Civil Code, and the Bankruptcy and Suspension of Debt Payment Obligations Law; secondary materials consist of relevant legal scholarship and professional literature. The materials are analysed qualitatively through systematic interpretation and prescriptive legal reasoning. The study finds that Indonesian law provides a sufficient normative basis for notarial involvement in corporate transactions, but it does not expressly integrate notaries into a formal bankruptcy-risk mitigation framework. In practice, preventive value arises from careful verification, precise allocation of corporate authority, balanced contractual drafting, dispute-resolution mechanisms, and legally sound restructuring instruments. Effectiveness nevertheless depends on regulatory coherence, professional competence, due care, legal awareness among business actors, and the quality of corporate legal governance. The article argues that corporate deeds should be treated not merely as evidentiary instruments, but as components of legal risk management capable of reducing dispute escalation and supporting business continuity.